The Influence of Manipulative Media Usage on Students' Understanding of Fraction Operations in Elementary Schools - Al Ayyubi, Ibnu Imam; Nurhikmah; Rahmawati, Siti; Trimulyati, Siti Hajar; Setiawati, Teti (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to analyze the influence of using manipulative media on students' understanding of fraction operations at MIS Muslimin Ciririp. A quantitative method with an explanatory approach was employed, involving 28 students selected through simple random sampling. The instruments used were questionnaires and tests. Data analysis included the Kolmogorov-Smirnov normality test, linearity test, as well as correlation and regression tests using SPSS version 26. The normality test results showed that the data were normally distributed, with significance values for manipulative media and fraction operation understanding of 0.064 and 0.200, respectively. The correlation test revealed a very strong relationship, with a correlation coefficient of 0.750, indicating a significant correlation between the use of manipulative media and students' understanding. The linear regression test produced the equation Y=47.186+0.479X, with a determination coefficient (R²) of 56.2%. This indicates that 56.2% of students' understanding of fraction operations is influenced by manipulative media, while the remaining 43.8% is influenced by other factors. This study confirms that the use of manipulative media significantly enhances students' understanding of fraction operations. These findings provide valuable insights for developing effective mathematics teaching strategies in elementary schools